2006
DOI: 10.1256/qj.05.197
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulations of three different MAP IOPs and the associated microphysical processes

Abstract: SUMMARYThe data collected during three contrasting Intensive Observing Periods (IOPs) of the Mesoscale Alpine Programme (MAP) were used to assess the performance of the Meso-NH model with particular emphasis on precipitation and microphysical processes. The model was able to reproduce the intense and moderate convective rain of IOPs 2A and 3, respectively, and also the stratiform precipitation associated with IOP 8. Microphysical budget computations were used to derive the mean vertical distribution of the hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 21 publications
1
70
0
Order By: Relevance
“…This potentially has a strong effect on the microphysics of orographic precipitation in this region by modulating the cloud condensation nuclei (CCN) spectrum (the so called indirect effect). Since both riming and collision of water droplets following coalescence is prerequisite for efficient precipitation (White et al, 2003;Lascaux et al, 2006;Rotunno and Houze, 2007), inhibition of this cloud microphysical process due to an increase in CCN concentration influences the precipitation efficiency of the system (Barros and Lettenmaier, 1994;Rosenfeld and Lensky, 1998;Khain et al, 2000;Ramanathan et al, 2001;Andreae et al, 2004;Tao et al, 2007;Lau et al, 2008;and many others). In order to study the aerosol indirect effect, a direct measurement of the CCN spectrum is required or, alternatively, it can be estimated from observed aerosol size distribution and chemical composition.…”
Section: P Shrestha Et Al: Pre-monsoon Aerosol Properties In Centramentioning
confidence: 99%
“…This potentially has a strong effect on the microphysics of orographic precipitation in this region by modulating the cloud condensation nuclei (CCN) spectrum (the so called indirect effect). Since both riming and collision of water droplets following coalescence is prerequisite for efficient precipitation (White et al, 2003;Lascaux et al, 2006;Rotunno and Houze, 2007), inhibition of this cloud microphysical process due to an increase in CCN concentration influences the precipitation efficiency of the system (Barros and Lettenmaier, 1994;Rosenfeld and Lensky, 1998;Khain et al, 2000;Ramanathan et al, 2001;Andreae et al, 2004;Tao et al, 2007;Lau et al, 2008;and many others). In order to study the aerosol indirect effect, a direct measurement of the CCN spectrum is required or, alternatively, it can be estimated from observed aerosol size distribution and chemical composition.…”
Section: P Shrestha Et Al: Pre-monsoon Aerosol Properties In Centramentioning
confidence: 99%
“…Finally, the MAP data were used to tune or improve the explicit microphysical schemes of some models. For example, Richard et al (2003) and Lascaux et al (2006) demonstrated that implementing a separate prognostic variable for hail (in addition to graupel) could be beneficial in cases of strong convection (IOP 2a).…”
Section: Model Improvements Triggered By Mapmentioning
confidence: 99%
“…The MOLOCH microphysics scheme is described in Drofa and Malguzzi (2004) but has recently been updated to include separate prognostic variables for graupel and hail. Information regarding the MESO-NH microphysical scheme can be found in Lascaux et al (2006). Figure 6 compares the accumulated precipitation fields computed with the different models.…”
Section: Model Intercomparisonmentioning
confidence: 99%
“…More advanced microphysics schemes often consider more water species, for instance by including graupel and/or hail (Lascaux et al, 2006), or by separating convective and nonconvective fractions of hydrometeors (Piriou et al, 2007). Also the fact that only six transfer mechanisms between the water species are possible is limiting.…”
Section: The Generalized Flux-conservative Equationsmentioning
confidence: 99%